2016
DOI: 10.1080/09513590.2016.1188375
|View full text |Cite
|
Sign up to set email alerts
|

Time lapse microscopy is useful for elective single-embryo transfer

Abstract: The aim of our study was to evaluate time lapse microscopy (TLM) as a selection tool for single-embryo transfer (SET) on day 5, blastocyst stage. An observational cohort study was conducted. Patients who had SET were compared to patients who had double embryo transfer (DET). A total of 108 patients were included in analysis, 83 had SET, and 25 underwent DET. Embryos were incubated and evaluated using TLM. The pregnancy rates were similar between the groups (42.2% in SET and 48.0% in DET). However, the multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 13 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…This might partially explain our result regarding the pregnancy rate with poor quality embryos. Perhaps more advanced methods to evaluate embryos, such as time lapse and genetic screening or pre-gestational screening (PGS) [10, 11] will provide a better definition of good and poor quality embryos and help to better predict viable pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…This might partially explain our result regarding the pregnancy rate with poor quality embryos. Perhaps more advanced methods to evaluate embryos, such as time lapse and genetic screening or pre-gestational screening (PGS) [10, 11] will provide a better definition of good and poor quality embryos and help to better predict viable pregnancies.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-five studies [ 2 , 11 , 13 , 15 , 21 , 24 , 28 31 , 38 , 39 , 43 , 44 , 48 – 50 , 53 , 54 , 56 59 , 62 , 64 , 66 69 , 72 , 75 – 77 , 79 81 , 85 87 , 91 , 93 96 , 98 ] were pooled and found that the MPR was significantly lower in the SET group than in the DET group (0.05, 0.04–0.06, I 2 = 2%, P < 0.001) (Supplementary Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A significant decrease in CPR (37.4% vs. 48.0%, 0.78, 0.71–0.85, I 2 = 82%, P < 0.001, n = 60) was noted in the SET group compared with the DET group [ 11 15 , 19 , 23 , 24 , 27 31 , 38 , 39 , 41 44 , 48 – 51 , 53 59 , 62 , 64 – 67 , 69 , 70 , 72 , 74 81 , 84 , 86 , 87 , 90 , 91 , 93 98 , 100 , 101 ]. Several subgroup analyses indicated a different direction, no differences of CPR were noted between SET and DET in subgroups of patients aged ≥40 years (0.88, 0.59–1.30, I 2 = 70%, n = 5), GQE versus GQE + PQE (1.01, 0.89–1.16, I 2 = 0%, n = 9), and frozen cycles (0.79, 0.62–1.00, I 2 = 83%, n = 9; Supplementary Table S3 , Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent reports have found a slight benefit in using blastocyst culture as compared to transfers at D2 or D3 [ 24 25 ]. Time lapse imaging, recently introduced in IVF laboratories, may represent the most promising non-invasive tool to determine embryo development in optimal conditions and to define predictive patterns correlated with high implantation potential [ 26 27 ]. Nevertheless, this system is not yet available in all IVF centres.…”
Section: Discussionmentioning
confidence: 99%